Mitochondria in apoptosis - Martinou, Jean-Claude (Henry Stewart Talks, 2007)
Cell death, Apoptosis, Mitochondria, Mitochondrial membrane permeabilization, Bcl-2, Bax, Permeability transition pore, Cytochrome c, Mechanistic explanations, Cancer, Degenerative diseases
Archived at 2021/10/31